Building Environmental Governance Knowledge through Environmental Culture in Schools: The Role of the Adiwiyata Program - Ulfa Durrota Aini Fedrya; Aldri Frinaldi (Al-Qalam Institue, 2025)
This research aims to explore the development of Environmental Governance Knowledge (EGK) through the integration of environmental culture in schools, with a focus on the Adiwiyata program. The study examines the process of building EGK and identifies both supporting and inhibiting factors in the program’s implementation. A qualitative approach with a descriptive method was employed, involving data collection through in-depth interviews, observations, and document analysis, which was validated through source and method triangulation. The data were analyzed through reduction, presentation, and conclusion drawing to identify patterns and relationships. The findings reveal that EGK development is facilitated through the establishment of Adiwiyata structures, curriculum integration, routine activities like community clean-ups, and the inclusion of local cultural and religious values. Supporting factors include local government assistance, active participation from teachers and students, and external partnerships. In contrast, challenges include low environmental awareness, limited facilities, and inconsistent program sustainability. The study concludes that while the Adiwiyata program has successfully promoted ecological awareness and strengthened environmental culture, its continued success depends on ongoing collaboration, sufficient resources, and sustained behavioral change.